ISLAM NUSANTARA DAN FILSAFAT ORIENTASI BANGSA; DIALEKTIKA MODERNITAS BERAGAMA DALAM NEGARA BERBUDAYA - Hijrian A. Prihantoro (Millah: Journal of Religious Studies, 2017)
Based on the pattern of relational dialectics, the relationship between Religion, Humanism and the Orientation of Nation should be understood as a single entity wich mutually reinforcing in achieving the ideal life of civil society. Indonesia as a country that recognizes the diversity of religion, language, ethnicity and culture has positioned the Pancasila as ideology of the state can not be contested legitimacy. NU as an social religious organization be aware of the Indonesian nation must be guarded sovereignty also dignity. Islam Nusantara as a religious idea of nationality strives to instill religion awareness in the state and nation. Its one important task is to unravel the roots of the conflict through awareness of ethics; ranging from Tyranny of the Majority issue to Human Rights issues in the application of the death penalty in Indonesian context. Therefore, this article head to examine the transformative process of religious values into a form of consciousness nationality oriented towards the sovereign and the dignity state.